2022
DOI: 10.1101/2022.03.22.485255
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targeted delivery of galunisertib attenuates fibrogenesis in an integratedex vivorenal transplant and fibrosis model

Abstract: Normothermic machine perfusion is an emerging preservation technique for kidney allografts to reduce post-transplant complications, including interstitial fibrosis and tubular atrophy. This technique, however, could be improved by adding antifibrotic molecules to perfusion solutions. We established Machine perfusion and Organ slices as a Platform for Ex vivo Drug delivery (MOPED), to explore fibrogenesis suppression strategies. We perfused porcine kidneys ex vivo with galunisertib, a potent inhibitor of the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…[10] However, even though cancer treatment has benefited from the NP-based formulations that have reached the market, only a few studies have investigated the delivery of galunisertib via NPs. [11,12] Therefore, the potential of galunisertib-loaded NPs for the oral treatment of CRC remains poorly explored. Our group demonstrated that the loading of galunisertib in gelatin-modified diatomite NPs (DNPs) enhances the antimetastatic effect of the drug in CRC cells due to a matrix metalloproteinase-triggered release from the gelatin matrix.…”
Section: Introductionmentioning
confidence: 99%
“…[10] However, even though cancer treatment has benefited from the NP-based formulations that have reached the market, only a few studies have investigated the delivery of galunisertib via NPs. [11,12] Therefore, the potential of galunisertib-loaded NPs for the oral treatment of CRC remains poorly explored. Our group demonstrated that the loading of galunisertib in gelatin-modified diatomite NPs (DNPs) enhances the antimetastatic effect of the drug in CRC cells due to a matrix metalloproteinase-triggered release from the gelatin matrix.…”
Section: Introductionmentioning
confidence: 99%